Statistics for quality control - Jackson, Daniel (Industrial Press, Inc., 2015)
This book is designed for trade schools, corporate training programs, technical and community colleges, or freshman level university students beginning a major in quality and quality management. Topics include: a brief background, measurements, and graphing techniques; beginning statistics necessary to understand these practices commonly found in industry; coverage of quality assurance issues along with some pertinent managerial practices associated with this topic. The "non-calculus" or "non-engineering" statistics in this book include the most common practices found in industrial settings regarding quality control statistics. Minitab & Excel data sets are used in many of the examples and home work problems. --